A Systematic Literature Review (SLR): Peran Model Discovery Learning dan Augmented Reality (AR) untuk Siswa Berkebutuhan Khusus - Ananda Dyah Khairunnisa; Winarto; Widowati, Asri; Roektiningroem, Ekosari; Rahayu, Dita Puji (Universitas Muhammadiyah Pontianak, 2026)
Students with special needs often have difficulty understanding science lessons due to limited exploration activities and a lack of direct experience. This study aims to analyze and describe efforts to improve science comprehension among students with special needs through the application of interactive Augmented Reality (AR) media and the Discovery Learning model. The articles used in this literature study were limited to those published between 2021 and 2025, with 20 articles selected from 60 identified articles from Google Scholar, ScienceDirect, Scopus and DOAJ. The method used was a Systematic Literature Review (SLR) with a Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) design. The results show that the use of the Discovery Learning model and augmented reality successfully improved students' cognitive skills but has not been widely applied in the learning of students with special needs. This study concludes that the Discovery Learning model and the application of Augmented Reality (AR) media require further development to be applied in the learning of students with special needs.